IMPLEMENTASI MANAJEMEN KOMISI PENYIARAN INDONESIA DALAM MENGAWAL ISI SIARAN TELEVISI - Intani, Retno (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Many interests dealing with television business effect on programs to gain demands of the market. Television programs are analogous to products or goods that are sold to other parties, in this case the audience and advertisers. The more audiences want goods (programs), the more interests that can influence on economy, social and cultural interests and also political interests. The implication is that goal of making programs are always directed to profit oriented. The Indonesian Broadcasting Commission (KPI) has its tasks to guarantee the community to have information that is appropriate and correct in accordance with human rights (Broadcasting Law 32/2002 Article 8 verse 3a). This study aims to determine the management implementation of the Indonesian Broadcasting Commission in monitoring and overseeing the content of Indonesian television broadcasting to establish healthy television programs. This study uses management theory consisting of planning, organizing actuating, controlling with constructive paradigms, qualitative approaches and descriptive methods. The results shows that KPI has implemented planning, organizing, actuating, controlling in carrying out the task of monitoring and overseeing television programs.